PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA ALL NEW JAZZ DI KOTA SEMARANG (Students' Journal of Economic and Management, 2015)
The aim ofthis study was toanalyze the effect ofbrand equityto the purchasing decisionHondaAll NewJazzin Semarang. The population inthis studyis that consumerswho buycarsHonda AllNewJazzin Semarang. The sample inthis studyas many as100 people. The sampling techniqueused purposive sampling. The criteria forthe samplein this studyis that consumerswho buycarsHonda AllNewJazzin Semarangfor at least 3months. The analytical toolusedis multiple linear regression. Results ofthe analysiscan be concludedthat: brandequitypositive influenceon purchase decisions.. Keywords: brand awareness, perceived quality, brand association, brand loyalty and purchasing decisions